LUMBAR SPINAL SUBARACHNOID BLOCK FOR CAESAREAN SECTION-A REVIEW OF 200 CASES - Gilani, Syed Mushtaq Ahmad; Ahmad, Bashir (Journal of Ayub Medical College Abbottabad, 1998)
Lumbar spinal subarachnoid block is simple, cheap and effective method of anaesthesia for infraumblical surgical procedures. In the present atmosphere of cost consciousness, spinal subarachnoid block is cost effective and can be of advantage in the developing countries like ours, where the medical gases and expert anesthesiologists are the rare commodities and deficiently available in the remote areas. Subarachnoid analgesia is entering into its centennial anniversary; this year as the first successful block was performed by August Bier in 1899 in Germany. In the present study the management of 200 cases of lower segment caesarian section under spinal subarachnoid block is presented and the advantages discussed. There was a low incidence of vomiting (9%) and no chances of aspiration even in the emergency nature of caesarian section. Cardiovascular side effects can be avoided by routine preloading with I. V fluids and the incidence of headache and backache can be reduced by using a small gauge L/P needle as is manifest in the present study. Spinal subarachnoid block has the advantage of the prolonged postoperative analgesia which can be prolonged further by adding narcotic analgesic to the local drug. In the present study, authors used hyperbaric local analgesic Cinchocaine (1:200 in 6 % glucose) which has a definite spread of analgesia. Spinal analgesia has the additional advantage of very low chances of foetal depression and the 84.47c babies born after caesarian section under spinal block has normal Apgar score. The authors would recommend lumber spinal subarachnoid block with all its advantages both on the maternal side as well as on the foetal side.